Assessment of meteorological, agricultural and hydrological droughts in Central Himalaya region under climate change - Li Wang; Fan Zhang; Xiaonan Shi; Chen Zeng; Yuxuan Xiang; Yafeng Wang (Journal of Hydrology: Regional Studies, 2025)
Study region: Gandaki River basin in the central Himalayan region. Study focus: Spatiotemporal investigation of meteorological, agricultural, and hydrological droughts over historical (1986–2014) and future periods (2024–2100). New hydrological insights for the region: Historical analysis reveals that meteorological, agricultural, and hydrological droughts exhibit an insignificant increase in severity and duration. Agricultural and hydrological droughts are characterized by higher severity and longer duration compared to meteorological droughts. Regarding the impact of precipitation and temperature on agricultural drought severity, precipitation replenishes soil moisture in various ways across different elevation zones, thereby alleviating agricultural drought. Conversely, temperature primarily intensifies agricultural drought severity by reducing soil moisture through evaporation and transpiration. Glaciers play an important role in hydrological drought, with both precipitation and temperature helping to alleviate drought severity in subbasins containing glaciers. This phenomenon is particularly pronounced for subbasins with a glacier area ratio exceeding 10.5 %, showcasing a significant negative correlation between temperature and drought severity. Future projections show that meteorological and agricultural droughts, particularly in elevation zones below 3000 m, which cover 79.4 % of agricultural land, will become more severe and prolonged, threatening agricultural productivity. Climate change and glacier retreat are expected to increase hydrological droughts' severity and duration. These findings enhance understanding of drought evolution and highlight the urgent need for drought planning and management to protect socio-economic development in the Central Himalaya.